The impact of functional training based on clinical nursing pathways informed by evidence-based theory on functional recovery in patients with cerebral hemorrhage - Liang, Haijuan; Yuan, Ping; Xu, Tong; Jin, Chao; Ji, Cuiling (Frontiers in Neurology, 2025)
BackgroundCerebral hemorrhage significantly impacts patients’ neurological function and daily living capabilities. The study investigates the effect of functional training based on clinical nursing pathways informed by evidence-based theory on the functional recovery in postoperative patients with cerebral hemorrhage.MethodsThis retrospective analysis included 160 patients divided into an intervention group receiving specialized functional training (n = 80) and a control group receiving standard care (n = 80) from December 2021 to December 2023. Functional recovery was evaluated using the National Institutes of Health Stroke Scale (NIHSS), Modified Barthel Index (MBI), and Glasgow Coma Scale (GCS). Complications and patient satisfaction were also assessed.ResultsThe intervention group showed significant improvements in NIHSS, MBI, and GCS scores post-intervention, indicating enhanced neurological function, daily living capabilities, and consciousness levels (p < 0.001). Complication rates were lower in the intervention group (2.5%) compared to the control group (18.75%), with statistical significance (p = 0.0021). Patient satisfaction was notably higher in the intervention group, with 95% total satisfaction compared to 76% in the control group (p < 0.01).ConclusionFunctional training within clinical nursing pathways, grounded in evidence-based theory, significantly improves postoperative functional recovery, reduces complications, and increases patient satisfaction in individuals recovering from cerebral hemorrhage.